St. Elmo's fire [videorecording (DVD)] - Estevez, Emilio, 1962-; Lowe, Rob; McCarthy, Andrew, 1962-; Schumacher, Joel, 1939-2020- (Columbia TriStar Home Entertainment, 2001)
Seven friends, recent college graduates, search for a place in the real world and face the issues of career and commitment. Against the backdrop of St. Elmo's, their local hang-out, they save, betray and love each one another as only the closest of friends can.